Evaluasi Kinerja Pelaksanaan Program Pembangunan Kehutanan dalam RPHJP di KPH Kayu Tangi - Setiawan , Muhammad Fariz; Nur, Muhammad Anshar (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2022)
The implementation of forestry development programs must be evaluated to achieve the targets that have been set during the forestry development implementation period. This study aims to determine the performance of forestry development and improvement strategies for implementing forestry development in the Long Term Forest Management Plan (LTFMP) in Forest Management Units (FMU). The data sources of this research are secondary data and primary data in the form of Tangi Timber Forest Management Unit (LTFMP) Long Term Management Plan (FMU) and interviews using a SWOT questionnaire. The data analysis technique used is program evaluation, namely comparing the plan with the realization of the implementation of forestry development and then analyzing with the Minister of Home Affairs Regulation No. 86 of 2017 to measure the performance interval in its implementation. And a SWOT analysis to determine strategies for improvement in the implementation of forestry development. This study indicates that the implementation of the forestry development program results in a predicate or achievement in 8 (eight) programs selected based on what can be measured in general that the implementation is still not optimal, so an improvement strategy is needed in its implementation. And for the improvement strategy, it is found that the most appropriate according to the circumstances is the S-O strategy, which is to use strength to take advantage of opportunities so that they can make targeted improvement policies.